(untitled) (De Rebus Antiquis, 2021)
In the History of Monasticism, the references to regular visits that village or town people paid to anchorites and coenobites in order to obtain spiritual guidance or even divine aid in the form of miracle are frequent. In contrast with it, the studies devoted to understanding the reasons for the displacement of the monks and its impact on the rural and urban everyday life are fewer, although such issue constitutes a promising approach regarding the social implications of monasticism, a movement that, even in a context of consolidation of coenobitism, that is to say, the sedentary monastic life, never gave up mobility, movement. In this article, we intend to reflect on the role played by the monks of Mt. Silpius in the Riot of Statues, which took place at Antioch, the metropolis of Syria-Coele, in February 387. Our main goal is to shed light on the relationship between the monks and the population around them, a peculiar characteristic of monasticism in Northern Syria, based on the homilies about the event delivered by John Chrysostom, then the main preacher of the Antiochene congregation.